Andalus Viewed by Spain, France and United States, Comparative Approach - José Antonio GONZÁLEZ ALCANTUD (Turath, 2024)
The Al-Andalus, as a transhistorical concept, but also as an embodiment of certain material realities –architecture, music-, has been subject to great intellectual and public attention for several centuries. In the contemporary world, this attention ranges from controversy in Spanish historical narrative, to French romanticization, to North American academic curiosity. The author, a specialist in the myth of Al-Andalus, moves through three realities, the Spanish, the French and the North American, to make a comparative exercise of the intellectual production on Al-Andalus, or some of its manifestations, to infer a horizon of postcolonial future. The turn of this must grant the word on Al-Andalus to its owners, be they Iberian, Maghrebi or Mediterranean.